2002
DOI: 10.1103/physreve.65.046121
|View full text |Cite
|
Sign up to set email alerts
|

Correlation functions near modulated and rough surfaces

Abstract: In a system with long-ranged correlations, the behavior of correlation functions is sensitive to the presence of a boundary. We show that surface deformations strongly modify this behavior as compared to a flat surface.The modified near surface correlations can be measured by scattering probes.To determine these correlations, we develop a perturbative calculation in the deformations in height from a flat surface. Detailed results are given for a regularly patterned surface, as well as for a self-affinely rough… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…These results in two dimensions have been interpreted in terms of a scale-dependent distribution of opening angles of the fractal boundary [259]. The same analogy has been evoked in the discussion of the surface critical behaviour of self-affine surfaces in [256,257].…”
Section: Semi-infinite Systems With Surface Imperfectionsmentioning
confidence: 63%
See 2 more Smart Citations
“…These results in two dimensions have been interpreted in terms of a scale-dependent distribution of opening angles of the fractal boundary [259]. The same analogy has been evoked in the discussion of the surface critical behaviour of self-affine surfaces in [256,257].…”
Section: Semi-infinite Systems With Surface Imperfectionsmentioning
confidence: 63%
“…Using a perturbative calculation in the deformations in height from a flat surface they showed that the leading power law decay of the correlations is the same as for a flat surface, but with a modulated amplitude reflecting the shape of the surface [256,257].…”
Section: Semi-infinite Systems With Surface Imperfectionsmentioning
confidence: 97%
See 1 more Smart Citation
“…General expression for correlation function G ðuÞ r; r 0 ð Þ ¼ũ uðrÞũ uðr 0 Þ h i can be obtained from the generating functional [17,18] ZfJg ¼ exp using auxiliary field J(r). With the help of Eq.…”
Section: Correlation Functions For Bounded Systems Of ''Correlated'mentioning
confidence: 99%
“…102=[1572]E. S. Pikina long-range correlations[18] (see Appendix C). The leading contribution to the two-dimensional Fourier transform of the correlation G…”
mentioning
confidence: 99%